Constraints on the evolution of the Triton atmosphere from occultations: 1989-2022 - Sicardy, B.; Tej, A.; Gomes-Júnior, A. R.; Romanov, F. D.; Bertrand, T.; Ashok, N. M.; Lellouch, E.; Morgado, B. E.; Assafin, M.; Desmars, J.; Camargo, J. I.B.; Kilic, Y.; et al. (EDP Sciences, 2024)
Context. In about 2000, the south pole of Triton experienced an extreme summer solstice that occurs every ~650 years, when the subsolar latitude reached about 50?S. Bracketing this epoch, a few occultations probed the Triton atmosphere in 1989, 1995, 1997, 2008, and 2017. A recent ground-based stellar occultation observed on 6 October 2022 provides a new measurement of the atmospheric pressure on Triton. This is presented here. Aims. The goal is to constrain the volatile transport models (VTMs) of the Triton atmosphere. The atmosphere is basically in vapor pressure equilibrium with the nitrogen ice at its surface. Methods. Fits to the occultation light curves yield the atmospheric pressure of Triton at the reference radius 1400 km, from which the surface pressure is deduced. Results. The fits provide a pressure p1400 = 1:211 ± 0:039 μ bar at radius 1400 km (47 km altitude), from which a surface pressure of psurf = 14:54 ± 0:47 μ bar is deduced (1s error bars). To within the error bars, this is identical to the pressure derived from the previous occultation of 5 October 2017, p1400 = 1:18±0:03 μ bar and psurf = 14:1±0:4 μ bar, respectively. Based on recent models of the volatile cycles of Triton, the overall evolution of the surface pressure over the last 30 years is consistent with N2 condensation taking place in the northern hemisphere. However, models typically predict a steady decrease in the surface pressure for the period 2005-2060, which is not confirmed by this observation. Complex surface-atmosphere interactions, such as ice albedo runaway and formation of local N2 frosts in the equatorial regions of Triton, could explain the relatively constant pressure between 2017 and 2022.
Keywords: Planets and satellites: atmospheres; Planets and satellites: individual: Triton